Evaluation of Polybrominated Diphenyl Ether Toxicity on HepG2 Cells – Hexabrominated Congener (BDE‐154) Is Less Toxic than Tetrabrominated Congener (BDE‐47). Issue 5 (12th June 2016) - Souza, Alecsandra O.; Tasso, Maria J.; Oliveira, Alana M. C.; Pereira, Lilian C.; Duarte, Filipe V.; Oliveira, Danielle P.; Palmeira, Carlos M.; Dorta, Daniel J.
Abstract: Apoptotic cell death is one of the main consequences of exposure to brominated flame retardants, including polybrominated diphenyl ethers. However, few of these compounds have had their potential toxicity investigated. BDE‐154 is one of the most poorly studied polybrominated diphenyl ether (PBDE) congeners, but its level in the environment and in biological fluids is rising. In addition, its chemical structure differs from the other congeners with well‐documented toxicity, so BDE‐154 may display a distinct toxicity pattern. This study has evaluated how BDE‐154 affects the human hepatoblastoma cell line (HepG2) and has looked into the impact of this congener on human health. In addition, this study has related the effects of BDE‐154 with the effects of BDE‐47 to clarify the mechanism of PBDE toxicity. The HepG2 cell line was exposed to BDEs for 24 and 48 hr and submitted to assays to examine proliferation, viability, mitochondrial membrane potential, reactive oxygen species accumulation, phosphatidylserine exposure, nuclear fragmentation and evaluation of pro‐caspase 3, pro‐caspase 9, cytochrome c release, and apoptosis inductor factor release by Western blot analysis. BDE‐154 induced mitochondrial damage and led to apoptotic death of HepG2 cells, but these effects were less intense than the effects promoted by BDE‐47. Unlike other extensively reported congeners, BDE‐154 was only toxic at the higher tested concentrations, whereas BDE‐47 cytotoxicity was evident even at lower concentrations. Hence, like the toxicity pattern of other classes of substances such as polychlorinated biphenyls, the toxicity pattern of BDEs also depends on their chemical structure and aromatic substituent.